Microbiological quality of commonly consumed street foods in Bangladesh. Issue 1 (8th February 2016) - Noor, Rashed
Abstract : Purpose: – The purpose of this review is to narrate the microbiological quality of variety of street foods which are largely consumed by the Bangladeshi people of all ages. However, these foods are prone to microbial contamination. Most of the vendors lack the awareness on hygiene during preparing, processing or handling the foods. The insufficiency in regular microbiological analysis further casts the possibility of disease onset. The need of microbial analyses of these foods also remains unclear to the consumers, which, in turn, results in microbial infections and intoxications remaining unnoticed. Design/methodology/approach: – The present review focused on the microbiological quality of the street foods projected from the locally conducted researches on street foods, and pondered on the possible management from a microbiological perspective for ensuring consumer safety. Findings: – This paper provides comprehensive information on the microbiological quality of street foods, requirement of maintenance of hygiene by the vendors and consumers and the necessity of adopting proper management during food preparation. Originality/value: – Demonstration of microbial prevalence in the street foods may bring imperative information on food safety and security. The conclusive message of this review is about the general consciousness on the microbiological aspects of street food contamination.